A Game Theory Approach for D2D Communication Mode Selection for Terminals under a Cell. (2022) - , Eric Michel Deussom Djomadji; Hawama, Axel Hawama; Basile, Kabiena Ivan; Sone, Michael Ekonde
No abstract available